Antibacterial Effectiveness Test of Kencur Rhizome Ethanol Extract (Kaempferia galanga L.) against Escherichia coli and Staphylococcus aureus - Rr Nadhira Al Fajrie; Nurhayani (HM Publisher, 2023)
Indonesia is a country with abundant biodiversity. Increased bacterial resistance Escherichia coli and Staphylococcus aureus antibiotics require alternative treatment, one of which is medicinal plants. Kencur (Kaempferia galanga L.) is a medicinal plant that contains saponins, flavonoids, phenols, and tannins, which can inhibit bacterial growth. This study aimed to determine the antibacterial effect of kencur rhizome ethanol extract (Kaempferia galanga L.) against Escherichia coli and Staphylococcus aureus. This research is an experimental laboratory design post-test only control group design. The rhizomes of kencur were extracted using 70% ethanol and tested for antibacterial activity using the well method. There were 6 groups in the study, namely the positive control group using ciprofloxacin, the negative control using distilled water, kencur rhizome ethanol extract concentrations of 12.5%, 25%, 50%, and 100%. The largest diameter of the inhibition zone was found at a concentration of 100%, with an average of 10.18 mm in the bacteria Escherichia coli and 22.47 mm in the bacteria Staphylococcus aureus. In conclusion, the ethanol extract of kencur rhizome (Kaempferia galanga L.) can inhibit the growth of bacteria Escherichia coli and Staphylococcus aureus.